Burden of mortality attributed to PM2.5 exposure in cities of Iran; contribution of short-term pollution peaks. (1st March 2020) - Hadei, Mostafa; Shahsavani, Abbas; Krzyzanowski, Michal; Querol, Xavier; Stafoggia, Massimo; Nazari, Seyed Saeed Hashemi; Jafari, Ahmad Jonidi; Yarahmadi, Maryam; Kermani, Majid; Khosravi, Ardeshir
Abstract: The objective of this study was to determine the population exposure to PM2.5, and to quantify the effect of eliminating short-term pollution peaks on the number of cause-specific deaths, the number of years of life lost (YLL), and economic losses attributed to exposure to PM2.5 in 25 Iranian cities with available air quality data. Number of deaths and YLL were estimated with AirQ + software tool using available concentration-response functions and life table approach. Furthermore, the value of lost life in each city were calculated using the Value of Statistical Life (VSL) method. Two scenarios were defined; Scenario A, considering actual observed concentrations to estimate the real health effects of PM2.5, and Scenario B, controlling for the effect of air pollution episodes. The results showed that the annual average concentrations of PM2.5 in cities were 1.5–6.1 times higher than the guideline value of WHO (10 μg/m³). The total number of all-cause deaths due to long-term exposure exceeding WHO air quality guideline level was 13321 (95% C.I.: 8837–17378) cases per year in all cities. The total numbers of chronic obstructive pulmonary disease (COPD), lung cancer, ischemic heart disease (IHD), and stroke deaths attributed to the exposure were 274, 315, 1536, and 963 cases, respectively. The total number of YLL over 10 years period in all 25 cities was 486, 289 years and the loss of life expectancy ranged from 0.43 to 1.87 years. The sum of economic losses due to lost life exceeded 5.8 billion USD. Except for some cities, avoiding highly polluted days in Scenario B would result in only 5% reduction in overall health or economic effects. These results indicate an urgent need for new comprehensive plans to tackle air pollution in Iranian cities focused on reduction of long term average pollution levels since programs for avoiding highly polluted days lead to a limited health benefits only. Highlights: In all cities, sum of all-cause deaths due to exposure to PM2.5 was 13321. In all cities, the total number of YLL was about 500, 000 years. The loss of life expectancy ranged from 0.43 to 1.87 years. The sum of economic losses due to lost life exceeded 5.8 billion USD. Avoiding highly polluted days resulted in only 5% reduction in health effects.